Розвиток методу та алгоритмів обробки фазових спостережень глобальних навігаційних супутникових систем в задачах високоточного кінематичного позиціонування - Желанов, О. О. (My University, 2011)
У дисертації розв’язано актуальну науково-прикладну задачу високоточного кінематичного позиціонування шляхом подальшого вдосконалення існуючих і створення нових однобазових і мережевих методів і алгоритмів обробки фазових і кодових спостережень двочастотних GPS/ГНСС- приймачів. При цьому було досягнуто субдециметрової/сантиметрової точності визначення місцеположення для кінематичного (3÷7 см (СКВ)) і статичного (2÷5 см (СКВ)) режиму зйомки на базових відстанях 150÷200 км. Достовірність наукових результатів і висновків, сформульованих у дисертації доведено, насамперед, експериментальною перевіркою основних наукових положень роботи. In the dissertation the actual scientific and applied problem of high-precision kinematic positioning is solved. The problem decision is based on modernization and development of single-base and multibase methods and algorithms of processing of phase and code observations of dual-frequency GPS/GNSS-receivers. The idea of dissertation consists in the following: - definition and realization of conditions of achievement of high reliability of phase ambiguity resolution (AR) of Wide Lane observations; - development of AR WL method and creations of new algorithms of processing of processing of phase difference frequency measurements. - achievement of subdecimeter/centimetric accuracy of positioning. The reached accuracy of positioning (RMS) on baselines 150÷200 km: - for a kinematic mode of 3-7 centimetres; - for a static mode of 2-5 centimetres. Validity of scientific results and conclusions formulated in the dissertation is proved, first of all, by experimental check of basic scientific positions of the work.
Keywords: Wide Lane; Melbourne-Wübbena; code-phase combination; verification; Wide Lane; Melbourne-Wübbena